Vaginal pressure sensor measurement during maximal voluntary pelvic floor contraction correlates with vaginal birth and pelvic organ prolapse—A pilot study - Parkinson, Luke A.; Karjalainen, Päivi K.; Mukherjee, Shayanti; Papageorgiou, Anthony W.; Kulkarni, Mugdha; Arkwright, John W.; Young, Natharnia; Werkmeister, Jerome A.; Davies‐Tuck, Miranda; Gargett, Caroline E.; Rosamilia, Anna (Neurourology and urodynamics, 2022)
Aims To measure the force applied along the anterior and posterior vaginal walls in a cohort of 46 patients measured by a fiber‐optic pressure sensor and determine if this correlates with vaginal parity and pelvic organ prolapse (POP). Methods An intravaginal fiber‐optic sensor measured pressure at nine locations along the anterior and posterior vaginal walls during a maximal voluntary pelvic floor muscle contraction (MVC). An automated probe dilation cycle measured the tissue resistance incorporating the vagina and surrounding anatomy. MVC and resting tissue resistance (RTR) were assessed between subjects grouped by the number of vaginal births and prolapse stage. Results A previous vaginal birth was associated with a significant threefold decrease in the overall anterior pressure measurement during MVC. Decreased anterior pressure measurements were observed at Sensors 1 and 3 (distal vagina) and, posteriorly at Sensors 4–6 (midvagina). Women with Stage 2 posterior prolapse exhibited a decreased MVC pressure in the midvagina than those with Stage 0/1. In this pilot study, there was no difference in the vaginal wall RTR according to previous vaginal birth or stage of prolapse. Conclusion This pilot study found that a decrease in vaginal pressure measured during MVC is associated with vaginal birth and with posterior POP. Greater sample size is required to assess the role of resting tissue pressure measurement.